Influence of limiting and regulating factors on populations of Asian citrus psyllid and the risk of insect and disease outbreaks - Udell, B. J.; Monzó, César; Paris, T. M.; Allan, S. A.; Stansly, Philip A. (Wiley Online Library, 2020)
Diaphorina citri, known as the Asian citrus psyllid (ACP), is the insect vector of a devastating citrus disease (huanglongbing; HLB), which has caused billions of dollars in damage in Florida since its detection in 2005. Data from long‐term monitoring programs in two Florida citrus groves were used to assess ACP demography and population ecology, which is needed to implement more effective management strategies for HLB. Seasonal patterns and correlations between ACP density estimates and a suite of environmental and community indicators, previously shown to influence ACP demography, were described and interpreted. Data were evaluated for evidence for spatial clustering and density‐dependent recruitment of ACP in a major outbreak event using Taylor power law analysis and by fitting a stochastic Beverton–Holt recruitment model using state‐space approach. Strong evidence for density‐dependent recruitment and spatial clustering was found and should be considered for future modelling work as it can greatly influence ACP populations by affecting their growth rates, dispersal behaviour and morphology, as well as HLB transmission. Observations of ACP density and dispersion in space and time, along with the estimated parameters from the Beverton–Holt model, suggested that intraspecific competition for resources may initiate both local, then widespread dispersal process, thus affecting grove‐wide and area‐wide HLB transmission. When these results were synthesised with those of parallel studies, the removal of several of these regulating factors in a single year could lead to widespread disease of the entire crop in a grove, and likely surrounding groves as well. We provide the first field evidence of the consequences of back‐to‐back ACP colonisation on the rapid spread of the HLB in a grove (a mechanism previously demonstrated in laboratory settings). We stress the importance of proper integrated pest management and area‐wide management to prevent such outbreaks.